2013
DOI: 10.1007/s10164-013-0388-7
|View full text |Cite
|
Sign up to set email alerts
|

Preference for meat is not innate in dogs

Abstract: Indian free-ranging dogs live in a carbohydrate-rich environment as scavengers in and around human settlements. They rarely hunt and consequently do not encounter rich sources of protein. Instead they have adapted to a diet of primarily carbohydrates. As descendents of the exclusively carnivorous wolves, they are subjected to the evolutionary load of a physiological demand for proteins. To meet their protein needs they resort to a thumb rule -if it smells like meat, eat it. Pups face high competition from grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Free-ranging dogs live in human dominated environments and heavily depend on humans for food (Bhadra et al, 2016; Bhadra and Bhadra, 2014). Apart from scavenging, they directly beg for food from humans (Bhadra and Bhadra, 2014; Sen Majumder et al, 2014). However, getting or retrieving food items can lead to consequences like beating and harassment, which probably have made these dogs opportunistic.…”
Section: Discussionmentioning
confidence: 99%
“…Free-ranging dogs live in human dominated environments and heavily depend on humans for food (Bhadra et al, 2016; Bhadra and Bhadra, 2014). Apart from scavenging, they directly beg for food from humans (Bhadra and Bhadra, 2014; Sen Majumder et al, 2014). However, getting or retrieving food items can lead to consequences like beating and harassment, which probably have made these dogs opportunistic.…”
Section: Discussionmentioning
confidence: 99%
“…Though free-ranging dogs tend to avoid direct human contact, studies have shown that they gaze and even seek help from strangers when faced with an unfamiliar task (Bhattacharjee et al, 2017a). Free-ranging dogs are also known to regularly beg from humans, using the gazing behaviour (Bhadra and Bhadra, 2014). They often experience negative interactions with humans, and their tendency to avoid direct physical contact with unfamiliar humans could be a possible outcome of cumulative negative experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Free-ranging dogs are found in most of the developing countries and live without direct human supervision (Cafazzo et al, 2010). They are primarily scavengers depending on human leftover food but also display occasional begging from humans (Bhadra and Bhadra, 2014;Sen Majumder et al, 2014). Free-ranging dogs interact with humans regularly and receive both positive (food, social petting, etc.)…”
Section: Introductionmentioning
confidence: 99%